2013
DOI: 10.18561/2179-5746/biotaamazonia.v3n1p94-99
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de Crustáceos Ectoparasitos no Peixe Ariacó, Lutjanus synagris (Linnaeus, 1758) nas Águas Costeiras do Rio Grande do Norte, Brasil

Abstract: RESUMO: O ariacó, Lutjanus synagris é um peixe marinho de grande valor comercial que contribui para a produção pesqueira artesanal do Rio Grande do Norte, Brasil. O presente estudo investigou a ocorrência de crustáceos ectoparasitos no peixe marinho L. synagris no litoral do Rio Grande do Norte. Foram capturados 100 exemplares de L. synagris nas águas costeiras do Rio Grande no Norte, no período de março de 2008 a fevereiro de 2009. Os hospedeiros apresentaram comprimento total variando de 6,35 a 26,46 cm (18,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
(1 reference statement)
2
6
0
3
Order By: Relevance
“…Bunkley-Williams et al (2006) reported low prevalences of R. signata in tomtate grunt Haemulon aurolineatum (0.45%), Corocoro grunt Orthopristis ruber (0.49%) and in glasseye Heteropriacanthus cruentatus (0.22%). In relation to mean intensity and abundance, similar values were found in M. argentinae , in L. synagris (Cavalcanti et al, 2013), in L. analis (Hermida et al, 2014), in C. crysos, O. saliens andT. lepturus (Carvalho-Souza et al, 2009) and in S. frondosum (Cavalcanti et al, 2012).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Bunkley-Williams et al (2006) reported low prevalences of R. signata in tomtate grunt Haemulon aurolineatum (0.45%), Corocoro grunt Orthopristis ruber (0.49%) and in glasseye Heteropriacanthus cruentatus (0.22%). In relation to mean intensity and abundance, similar values were found in M. argentinae , in L. synagris (Cavalcanti et al, 2013), in L. analis (Hermida et al, 2014), in C. crysos, O. saliens andT. lepturus (Carvalho-Souza et al, 2009) and in S. frondosum (Cavalcanti et al, 2012).…”
Section: Discussionsupporting
confidence: 56%
“…This study showed similar values of infestation when compared to other fish species. Slightly higher prevalence in the spotted goatfish herein studied was observed in comparison to M. argentinae , lane snapper Lutjanus synagris (Cavalcanti et al, 2013), mutton snapper Lutjanus analis (Hermida et al, 2014), blue runner Caranx crysos, castin leatherjacket Oligoplites saliens and largehead hairtail Trichiurus lepturus (Carvalho-Souza et al, 2009), and the former have reported by the first time its occurrence in the Baía de Cotegipe, Bahia, Northeast Brazil. Contrarily to that observed in this study, high prevalence rates were found in Spanish mackerel Scomberomorus brasiliensis and in parrotfish Sparisoma frondosum from the Rio Grande do Norte (Lima et al, 2005;Cavalcanti et al, 2012).…”
Section: Discussionmentioning
confidence: 62%
“…Lima et al [22] recorded isopods in Scomberomorus brasiliensis Collette, Russo & Zavala-Camin, 1978 and found R. signata in 31% of parasitized fish. Other authors also reported the presence of the parasite in Lutjanidae (snappers) including Cavalcanti et al [23] that recorded R. signata in L. synagris with 10% of parasitized fish and a mean intensity of 1.25. The parasite has a distribution from Central America to South America, and has been recorded by Hermida et al [24] in L. analis , corroborating the registry in the same host of the present study, these authors showed a prevalence of 3.3% and an average intensity of 1.00.…”
Section: Resultsmentioning
confidence: 95%
“…Despite the great diversity of marine fish and their economic importance, studies about the impact of parasites on the health of marine ichthyofauna in Brazil are scarce (Pavanelli et al, 2008). These studies do not exist for the northeastern region of Brazil, where the research already carried out so far has been restricted to the taxonomic identification and occurrence of marine fish parasites (Cavalcanti et al, 2013a(Cavalcanti et al, , 2013bHermida et al, 2014;Alves et al, 2018Alves et al, , 2020Cardoso et al, 2018).…”
Section: Introductionmentioning
confidence: 99%